(untitled) (Research, Society and Development, 2022)
Food supplements are products composed mainly of vitamins, minerals, plant stracts, tissue extracts, tissue extracts, proteins and amino acids, or the combination of these different elements, usually administered orally to complement a specific nutritional deficiency and assist in development by providing the improvement of the physical performance of an individual. As a result, the objective of this study was to evaluate the nutritional aspects related to food supplementation, as well as the risks and benefits of its use. The methodology used in the present is in a descriptive/exploratory, documentary way, of the systematic review type. The data collection of the articles was carried out during the period from February 24, 2021 to October 8, 2021, using as a database the Online platform for Search and Analysis of Medical Literature (Medline), Scientifc Electronic Library Online (Scielo) and Latin American and Caribbean Literature in Health Sciences (Lilacs) and Virtual Library in Health (BVS). Thus, from the data collected it was possible to realize that the choice of the foods that make up the diet of coaches and athletes is fundamental for the maintenance of the health of these individuals, but also for non-athletes, as a form of weight control and body composition. In this sense, there is evidence that the use of nutritional supplements has grown, for the up for the purposes of hypertrophy, elimination of excess body fat. For the use of a certain nutritional supplement it is necessary to undergo a medical evaluation in order to establish the amount and which appropriate supplement.